The neural basis of phantom limb pain - Flor, Herta; Diers, Martin; Andoh, Jamila (Trends in cognitive sciences, 2013)
A recent study suggests that brain changes in amputees may be pain-induced, questioning maladaptive plasticity as a neural basis of phantom pain. These findings add valuable information on cortical reorganization after amputation. We suggest further lines of research to clarify the mechanisms that underlie phantom pain.
Gesehen am 15.04.2021